Curcumin reduces the expression of interleukin 1β and the production of interleukin 6 and tumor necrosis factor alpha by M1 macrophages from patients with Behcet's disease. (4th July 2018) - Palizgir, Mohammad Taghi; Akhtari, Maryam; Mahmoudi, Mahdi; Mostafaei, Shayan; Rezaiemanesh, Alireza; Shahram, Farhad
Abstract: Objective: Behcet's disease (BD) is an auto-inflammatory disorder. Curcumin as a bio-active agent has anti-inflammatory properties. Effects of curcumin on the pathogenesis of BD are still not clear. In this study, we investigated the effect of curcumin on the inflammatory cytokines expression and production in M1 macrophages from BD patients compared with healthy controls. Methods: Monocytes were collected from 10 healthy controls and 20 active BD patients, differentiated to macrophages by macrophage-colony stimulating factor for 7 d. Macrophages were then treated with interferon gamma, lipopolysaccharide, and curcumin (10 or 30 µg/ml) for 24 h. Analysis of tumor necrosis factor-alpha (TNFα), interleukin 1β (IL-1β), and IL-6 mRNA expression and protein production was performed using SYBR Green qPCR and ELISA method. Results: Treatment with 30 µg/ml curcumin significantly down-regulated mRNA expression of IL-1β ( p <  .05) and protein production of IL-6 ( p  < .05) in M1 macrophages from BD patients but not in M1 macrophage from controls. Treatment with 30 µg/ml curcumin also significantly diminishes the protein production of TNFα in BD patients ( p  < .01) and healthy controls ( p  < .05) M1 macrophages. Conclusions: We demonstrated that curcumin can inhibit the expression and production of inflammatory cytokines in M1 macrophages from BD patients. Our results suggest that curcumin can modulate inflammatory signaling more specifically in macrophages from BD patients than healthy macrophages.